Structure peculiarities of three- and four-cluster nuclei 6He, 6Li, and 10Be, 10C - B. E. Grinyuk; I. V. Simenog (Ядерна фізика та енергетика)
Within a three-particle model (α + N + N), structure peculiarities of 6He and 6Li halo nuclei are studied. Within a four-particle model (α + α + N + N), the structure of 10Be and 10С nuclei is analized and compared with that of 6He and 6Li. The charge density distributions and form factors of these nuclei are calculated and explained. The density distributions of extra nucleons in 10Be and 10С are studied and compared with the calculated distributions of halo nucleons in 6He and 6Li. A detailed study of the asymptotics of the density distributions is carried out for the threeparticle 6He and 6Li nuclei. Asymptotic behavior of the amplitudes of clusterization is analyzed, and the coefficients of clusterization are calculated for the deuteron cluster in 6Li and the dineutron cluster in 6He. The variational method with optimized Gaussian bases is used in calculations.